Psychological sense of community as mediator and growth mindset as moderator in the impact of institutional integrity and perceived teacher support on student thriving: Evidence from private universities in China. - Yujun Jiang; Huying Liu; Zhiqun Ouyang; Meng Xie; Shihang Wei (PLoS ONE)
Previous research may have focused more on the direct rather than indirect effects of psychological characteristics on student success. This study explored the mediating effect of psychological sense of community and the moderating effect of growth mindset on the impacts of institutional integrity and perceived teacher support on student thriving in academic, interpersonal, and psychological domains. The hypothesized research model was proposed based on the Thriving Model, and the study was carried out in the setting of private universities in China. This study employed a partial least squares structural equation modeling (PLS-SEM) approach, obtaining a total of 1792 valid questionnaire responses through an online survey. The research highlights that psychological sense of community plays a crucial role in mediating the impact of institutional integrity and perceived teacher support on student thriving. In addition, it was found that growth mindset positively moderates the impact of institutional integrity and perceived teacher support on student thriving. Some implications and recommendations for teachers, administrators, and researchers in relevant fields were provided.